Agrarian Legislations and Movements as Sources of Change The Case of Kerala - T\K Oommen (ECONOMIC AND POLITICAL WEEKLY 1975, 1975)
That the routes to social change can be many is widely recognised in social science literature. In this article, the author discusses social legislations and protest movements as sources of social change. But whether or not the desired goal - realisation of change - will ho. achieved through legislations or movements, depends on the nature of the stratification, power-structure, and cultural system in a society. The main concern here is to examine the relationship between agrarian legislations and movements with special reference to Kerala' Kerala is a critical case in the Indian context, as radical agrarian legislations were enacted and militant movements initiated, in this state.